Risks of Undersizing Stent Retriever Length Relative to Thrombus Length in Patients with Acute Ischemic Stroke - Belachew, N.F.; Dobrocky, T.; Meinel, T.R.; Hakim, A.; Vynckier, J.; Arnold, M.; Seiffge, D.J.; Wiest, R.; Piechowiak, E.I.; Fischer, U.; Gralla, J.; Mordasini, P.; et al. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Results regarding the association of thrombus length, stent retriever length, and recanalization success in patients with acute ischemic stroke are inconsistent. We hypothesized that the ratio of thrombus length to stent retriever length may be of particular relevance.MATERIALS AND METHODS: Patients with acute ischemic stroke undergoing stent retriever thrombectomy at our institution between January 2010 and December 2018 were reviewed retrospectively. Thrombus length was assessed by measuring the susceptibility vessel sign on SWI using a 1.5T or 3T MR imaging scanner. Multivariable logistic regression models were used to determine the association between thrombus length, stent retriever length, and thrombus length/stent retriever length ratio with first-pass recanalization, overall recanalization, and embolization in new territories. Results are shown as adjusted ORs with 95% CIs. Additional mediation analyses were performed to test for indirect effects on first-pass recanalization and overall recanalization success.RESULTS: The main analysis included 418 patients (mean age, 74.9 years). Increasing stent retriever length was associated with first-pass recanalization. Decreasing thrombus length and lower thrombus length/stent retriever length ratios were associated with first-pass recanalization and overall recanalization. Thrombus length and stent retriever length showed no association with first-pass recanalization or overall recanalization once thrombus length/stent retriever length ratio was factored in, while thrombus length/stent retriever length ratio remained a significant factor in both models (adjusted OR, 0.316 [95% CI, 0.112–0.892]; P = .030 and adjusted OR, = 0.366 [95% CI, 0.194–0.689]; P = .002). Mediation analyses showed that decreasing thrombus length and increasing stent retriever length had a significant indirect effect on first-pass recanalization mediated through thrombus length/stent retriever length ratio. The only parameter associated with embolization in new territories was an increasing thrombus length/stent retriever length ratio (adjusted OR, 5.079 [95% CI, 1.332–19.362]; P = .017).CONCLUSIONS: Information about thrombus and stent length is more valuable when combined. High thrombus length/stent retriever length ratios, which may raise the risk of unsuccessful recanalization and embolization in new territories, should be avoided by adapting stent retriever selection to thrombus length whenever possible.aORadjusted ORENTembolization into unaffected (new) territorieseTICIexpanded TICIFPfirst-passFPRfirst-pass recanalizationSLstent retriever lengthSVSsusceptibility vessel signTLthrombus length